Mammalian G1- and S-phase checkpoints in response to DNA damage - Bártek, Jiří; Lukáš, Jiří (Current opinion in cell biology, 2001)
The ability to preserve genomic integrity is a fundamental feature of life. Recent findings regarding the molecular basis of the cell-cycle checkpoint responses of mammalian cells to genotoxic stress have converged into a two-wave concept of the G1 checkpoint, and shed light on the so-far elusive intra-S-phase checkpoint. Rapidly operating cascades that target the Cdc25A phosphatase appear central in both the initiation wave of the G1 checkpoint (preceding the p53-mediated maintenance wave) and the transient intra-S-phase response. Multiple links between defects in the G1/S checkpoints, genomic instability and oncogenesis are emerging, as are new challenges and hopes raised by this knowledge.
Keywords: transkripční faktory; DNA Damage; Models, Biological; nádory; S fáze; G1 Phase; předpověď; zvířata; cdc25 Phosphatases; G1 fáze; Forecasting; fosfatasy cdc25; poškození DNA; proteinkinasy; nádorový supresorový protein p53; Neoplasms; Protein Kinases; Animals; Tumor Suppressor Protein p53; biologické modely; Transcription Factors; S Phase